Dimensi Akhlak dalam Filsafat Islam - Rasyad Rasyad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
History notes that Muslim philosophers do not only merely discusses about philosophy, but they are also fluent in ethics. The last mentioned discourse is even one of most important topics in their philosophical discourses. The importance of ethics is reflected in the work of Al-Farabi, Ibnu Sina, Ibnu Maskawaih, Ibnu Bajjah, Al-Ghazali and others. Their discourses on ethics conclude with predomination and the happiness, which all of them are related to one’s faith attitude and behaviour. The concepts of ethics that the Muslim philosophers proposed are interesting and have more chance to be actualised in large aspect of daily life. In general, they divide ethic into three categories; courage, karam, and ‘iffah. For them, these concepts could be actualised through social interaction both in community and even in larger space, state. This article explains these ethical dimensions according to Al-Farabi, Ibnu Sina, Ibnu Maskawaih, Ibnu Bajjah, dan al-Ghazali.